Previous pregnancy outcomes and subsequent pregnancy anxiety in a Quebec prospective cohort - Gabriel D. Shapiro; Jean R. Séguin; Gina Muckle; Patricia Monnier; William D. Fraser (Taylor & Francis Group, 2017)
Introduction: Pregnancy anxiety is an important psychosocial risk factor that may be more strongly associated with adverse birth outcomes than other measures of stress. Better understanding of the upstream predictors and causes of pregnancy anxiety could help to identify high-risk women for adverse maternal and infant outcomes. The objective of the present study was to measure the associations between five past pregnancy outcomes (live preterm birth (PTB), live term birth, miscarriage at <20 weeks, stillbirth at ≥20 weeks, and elective abortion) and pregnancy anxiety at three trimesters in a subsequent pregnancy. Methods: Analyses were conducted using data from the 3D Cohort Study, a Canadian birth cohort. Data on maternal demographic characteristics and pregnancy history for each known previous pregnancy were collected via interviewer-administered questionnaires at study entry. Pregnancy anxiety for the index study pregnancy was measured prospectively by self-administered questionnaire following three prenatal study visits. Results: Of 2366 participants in the 3D Study, 1505 had at least one previous pregnancy. In linear regression analyses with adjustment for confounding variables, prior live term birth was associated with lower pregnancy anxiety in all three trimesters, whereas prior miscarriage was significantly associated with higher pregnancy anxiety in the first trimester. Prior stillbirth was associated with greater pregnancy anxiety in the third trimester. Prior elective abortion was significantly associated with higher pregnancy anxiety scores in the first and second trimesters, with an association of similar magnitude observed in the third trimester. Discussion: Our findings suggest that the outcomes of previous pregnancies should be incorporated, along with demographic and psychosocial characteristics, into conceptual models framing pregnancy anxiety.